I'm a mother, therefore I question": Parents' legitimation sources of and hesitancy towards early childhood vaccination. (August 2021) - Çelik, Kezban; Turan, Sevgi; Üner, Sarp
Abstract: This study was conducted with mothers living in Ankara and registered in the year 2019 with the Immunization Services Unit of the Provincial Directorate of Health as cases of vaccine refusal. This qualitative study used semi-structured interviews to understand how mothers decide about child vaccination and the attitudes, perceptions, and beliefs underlying these decisions. A total of 23 interviews were conducted by two of the authors between March and September 2019. Each of the 23 participants had at least one child aged five years or younger and were living in Ankara. The study shows that mothers with vaccine hesitancy constitute a heterogeneous group whose members have differing levels of hesitation and concern about the vaccination of their children. It is also observed that the most important factor that affects their decisions is related to trust. Highlights: Mothers with vaccine hesitancy constitute a heterogenous group. Anti-vaccine campaigns use the internet very effectively. The most important factor that affects mother's decisions is related to trust. Building confidence in vaccines is a public service provision and public duty.